Association between Attention and Heart Rate Fluctuations in Pathological Worriers - Gazzellini, Simone; Dettori, Maria; Amadori, Francesca; Paoli, Barbara; Napolitano, Antonio; Mancini, Francesco; Ottaviani, Cristina (Frontiers in Human Neuroscience, 2016)
Recent data suggests that several psychopathological conditions are associated with alterations in the variability of behavioral and physiological responses. Pathological worry, defined as the cognitive representation of a potential threat, has been associated with reduced variability of heart beat oscillations (i.e., decreased heart rate variability; HRV) and lapses of attention indexed by reaction times (RTs). Clinical populations with attention deficit show RTs oscillation around 0.05 and 0.01 Hz when performing a sustained attention task. We tested the hypothesis that people who are prone to worry do it in a predictable oscillating pattern revealed through recurrent lapses in attention and concomitant oscillating HRV. Sixty healthy young adults (50% women) were recruited: 30 exceeded the clinical cut-off on the Penn State Worry Questionnaire (High-Worry); the remaining 30 constituted the Low-Worry group. After a diagnostic assessment, participants performed two 15-minute sustained attention tasks, interspersed by a standardized worry-induction procedure. RTs, HRV, and moods were assessed. The analyses of the frequency spectrum showed that the High-Worry group presents a significant higher and constant peak of RTs oscillation around 0.01 Hz (period 100 s) after the induction of worry, in comparison with their baseline and with the Low-Worry group that was not responsive to the induction procedure. Physiologically, the induction significantly reduced high-frequency HRV and such reduction was associated with levels of self-reported worry. Results are coherent with the oscillatory nature of the default mode network and further confirm an association between cognitive rigidity and autonomic nervous system inflexibility.